Potensi Senyawa Bioaktif Andrographolide Pada Daun Sambiloto (Andrographis paniculata) Sebagai Kandidat Anti Photo-Aging Secara In Silico - Zuhriyah, Nur; Fatkhurrohman, Fajar; Aida, Monika; Apriliani, Sindi; Setiyono, Eko (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Skin aging caused by UV radiation has become a growing concern among the Indonesian population. The effects of UV-induced skin aging can be mitigated by antioxidant compounds. Although synthetic antioxidants are commonly used to combat aging, their long-term use is discouraged due to potential systemic side effects and carcinogenic risks. Therefore, natural antioxidant compounds are needed as a safer alternative. Andrographis paniculata, known as Sambiloto, contains a natural antioxidant compound called andrographolide. This study aims to evaluate the potential of andrographolide by determining its binding affinity toward target protein receptors involved in the photoaging mechanism triggered by increased levels of Reactive Oxygen Species (ROS). Through in silico analysis, the potential of andrographolide was assessed using reverse docking techniques with databases such as PubChem, PharmMapper, SwissTargetPrediction, SuperPred, and PASS Online. Subsequent molecular docking was performed using PyRx 0.8 and PyMol software. The in silico data revealed interactions between the ligand compound and its receptors, including binding activity and binding positions based on hydrophobic interactions and hydrogen bonds, which were further analyzed. The results showed that andrographolide binds effectively to the IL-1, NF-κB, and IL-6 receptors with relatively low binding affinities of -7.5 (IL-1), -6.6 (NF-κB), and -6.5 (IL-6). Low binding affinity indicates stronger and more stable interactions between the ligand and receptor. Based on the results, andrographolide from A. paniculata exhibits promising potential as a candidate for anti-photoaging agents that can serve as an alternative to synthetic antioxidants.